Health-Related and Psychosocial Factors Associated with Prostate Cancer Stage at Diagnosis among Males Participating in Alberta’s Tomorrow Project - Michelle L. Aktary; Brittany Shewchuk; Qinggang Wang; Eric Hyndman; Lorraine Shack; Paula J. Robson; Karen A. Kopciuk (Prostate Cancer)
Prostate cancer (PCa) stage at diagnosis is an important predictor of cancer prognosis. In Canada, over one-quarter of males are diagnosed with advanced-stage PCa. Studies have identified several factors associated with PCa stage at diagnosis; however, evidence from Canada is limited. This study aimed to examine associations between sociodemographic characteristics, health history, health practices, and psychosocial factors and PCa stage at diagnosis among males participating in Alberta’s Tomorrow Project (ATP), a prospective cohort in Alberta, Canada. The study included males aged 35–69 years who developed PCa until January 2018. Factors associated with PCa stage at diagnosis were examined using partial proportional odds (PPO) ordinal regression models. A total of 410 males were diagnosed with PCa over the study period. A higher number of lifetime prostate-specific antigen tests were associated with earlier-stage PCa (OR 0.91, p = 0.02, 95% CI 0.83–0.99), while higher abdominal circumference (OR 1.02, p = 0.05, 95% CI 1.00–1.03), lower social support (OR 2.34, p < 0.01, 95% CI 1.31–4.17), and having children (OR 2.67, p < 0.01, 95% CI 1.38–5.16) were associated with later-stage disease. This study identified factors previously found in the literature as well as novel factors associated with PCa stage at diagnosis, which can help inform targets for cancer prevention programs to improve PCa prognosis.